2001
DOI: 10.1038/sj.cdd.4400884
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase inhibitors attenuate necrotic but not apoptotic neuronal death in experimental models of cerebral ischemia

Abstract: An excessive activation of poly(ADP-ribose) polymerase (PARP) has been proposed to play a key role in postischemic neuronal death. We examined the neuroprotective effects of the PARP inhibitors benzamide, 6(5H)-phenanthridinone, and 3,4-dihydro-5-[4-1(1-piperidinyl)buthoxy]-1(2H)-isoquinolinone in three rodent models of cerebral ischemia. Increasing concentrations of the three PARP inhibitors attenuated neuronal injury induced by 60 min oxygen-glucose deprivation (OGD) in mixed cortical cell cultures, but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 71 publications
5
93
1
2
Order By: Relevance
“…In our model of sublethal OGD, the PARP inhibitor DPQ was not able to reduce in a significant manner the release of LDH induced by the pseudo-ischemic insult. This finding may appear to be in contrast with previous results from our laboratory showing that PARP inhibitors are neuroprotective in cortical cell cultures exposed to OGD (Moroni et al, 2001). It should be noted, however, that OGD exposure in the present study was much milder (40 vs. 60 min) and that PARP inhibitors are known to be efficacious only when excitotoxic or ischemic insults are particularly intense and presumably necrotic (Bonfoco et al, 1995;Meli et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our model of sublethal OGD, the PARP inhibitor DPQ was not able to reduce in a significant manner the release of LDH induced by the pseudo-ischemic insult. This finding may appear to be in contrast with previous results from our laboratory showing that PARP inhibitors are neuroprotective in cortical cell cultures exposed to OGD (Moroni et al, 2001). It should be noted, however, that OGD exposure in the present study was much milder (40 vs. 60 min) and that PARP inhibitors are known to be efficacious only when excitotoxic or ischemic insults are particularly intense and presumably necrotic (Bonfoco et al, 1995;Meli et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…A large body of evidence demonstrates that the increased neoformation of PAR plays a crucial role in neurodegeneration. In models of cerebral ischemia and excitotoxicity, it appears that intracellular depletion of ATP induced by PARP-1 leads to energy failure and necrotic neuronal death (Ha and Snyder, 1999;Meli et al, 2004;Moroni et al, 2001). In contrast, during the caspase-dependent apoptotic process, PARP-1 is proteolytically cleaved and inactivated by caspase-3, a process that is widely used as an apoptotic marker (Oliver et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the possible neuroprotective effects of Bv8 we carried out experiments in cultured murine cortical cells exposed to OGD, an in vitro model of focal cerebral ischemia routinely used in our lab (Pellegrini-Giampietro et al, 1999a). We have demonstrated that OGD induces necrotic neuronal death in this system, as detected by the appareance of necrotic ultrastructural features 24 h later and the lack of caspase-3 activation (Moroni et al, 2001). As previously shown, exposure to OGD for 60 min produced an intermediate level of neuronal damage in this system: the release of LDH was approximately 75% of that observed by exposing the cultures to a high concentration of glutamate (1 mM) for 24 h, which elicited complete neuronal cell death.…”
Section: Resultsmentioning
confidence: 99%
“…namely rat organotypic hippocampal slices exposed to 30 min OGD, which produces selective CA1 injury 24 h later and the appearance of morphological characteristics of apoptosis, caspase-3 activation and PARP-1 cleavage (Moroni et al, 2001;Gerace et al, 2012b). Fig.…”
Section: Resultsmentioning
confidence: 99%